Perilaku Petani dalam Menerapkan Teknologi BP3T (Bakteri Perakaran Pemacu Pertumbuhan Tanaman) Pupuk Kandang untuk Tanaman Kakao di Kabupaten Limapuluh Kota - Halitur Rahma; Sri Wahyuni; Jumsu Trisno (Jurnal Penyuluhan, 2019)
Vascular streak dieback (VSD) is a deadly disease of cocoa because it attacks the vascular tissue growing point. RGBGP Technology (Root Growth Based Growth Plants) manure is designed to help control the disease while helping grow cocoa plants. This research aims to examine the behavior of cocoa farmers in applying RGBGP technology package of manure that is allegedly formed due to individual characteristics and innovation characteristics. This research was designed descriptively qualitative located in Limapuluh Kota District. Sampling was conducted by census, 43 people belonging to 4 selected farmer groups, namely Aroma, Inovasi, Buah Lobek, and Maju Sejahtera. The results show that farmers' behavior generally shows the willingness to implement RGBGP package of manure in the long term, supported by the relative advantages of innovation, accessible resources, easy to do and applied technology, observable results, and no significant constraints. However, attitudes are not related to individual characteristics of farmers consisting of formal education, nonformal education, experience of farming, land status, land area, main occupation, and gender.